Desain Informasi Cara Bayar Penerimaan Negara menggunakan Pemodelan Finite State Automata - Mahmud Mahmud; Windu Gata; Jordy Lasmana Putra; Hafifah Bella Novitasari; Suwanda Aditya Saputra (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
The government modernizes the state revenue system by launching the State Revenue Module (MPN), which connects the billing code generation system with the payment system at the collecting agent. This study aims to develop an information system on how to pay state revenues to assist the public in depositing state revenues through payment channels at the collecting agent by applying the Finite State Automata (FSA) modeling concept. The system development uses the waterfall model while collecting the agent's data. The FSA design and testing phase uses the JFLAP application, while the application design stage uses the Laravel framework. System testing uses the black box testing method to determine how far the functioning of the components or menus on the system has come. In addition to making it easier for the public to deposit state revenues, this study also shows that automata theory can help design a payment information application system. This application design offers a website display of information on how to pay state revenues that can run well. Every menu on the system, when used, has no errors so that this system can be utilized by users and developed in applications based on Android and iOS.